Analysis of the agroindustrial enterprise competitive strategy tools. Issue 2 (August 2019) - Fedorova, N V; Kukartsev, V V; Tynchenko, V S; Nikiforova, C E; Sadovskiy, I D; Ogol, A R
Abstract: The article presents an analysis of the agrarian enterprise competitive strategy. Considered ways to reduce costs. One of the most important tasks of enterprises is being solved - reducing costs. Several options have been identified for implementing this strategy, as well as difficulties in achieving this goal, and ways have been found to solve them. In addition, the main types of losses that occur in modern enterprises are highlighted and the essence of these losses is determined. The author gives a definition of cost and reveals the value of this indicator in the enterprise management system, determines the goals of cost reduction, and highlights the factors and methods of reducing the cost of production in the enterprise. He gives advice on how to start saving, how to reduce the cost of production and how to produce better products, while reducing the number of defects. Today, innovation has become a crucial tool for competing in global markets. To improve the skills in the field of innovation, it is necessary to ensure consistently high results by constantly introducing innovations and get high returns on them. The article reveals the peculiarity of introducing total innovations, their influence for organizations and the most important tools for introducing innovations, and considers five "puzzle pieces".